The Securities Industry Act 1983: An Overview - Khaw, Lake Tee (Journal of Malaysian and Comparative Law, 2019)
The Securities Industry Act 1983 (hereinafter referred to as the '1983 Act') was brought into effect on 7 July 1983. It replaces te Securities Industry Act 1973 (hereinafter referred to as the 1973 Act), which introduced for the first time some degree of regulation in the form of governmental control in the running of the stock exchange and the securities industry as a whole in Malaysia. Basically, the 1983 Act retains the framework of its predecessor although several new and distinct features have been introduced. The new salient features of the 1983 Act include the setting up of the Capital Issues Committee (hereinafter the "C.I.C"), the Registrar's powers of investigation and enforcement and the introduction of new penal provisions relating to trade in securities. Most, if not all, of the provisions in th 1983 Act are modelled very closely on the Australian Securities Industry Act, 1980.